Ultrasound for diagnosis of postpartum retained products of conception-How accurate we are? - Yael Yagur; Liron Jurman; Omer Weitzner; Nissim Arbib; Ofer Markovitch; Zvi Klein; Yair Daykan; Ron Schonman (BMC, 2023)
Abstract Objective Postpartum retained products of conception (RPOC) can cause short- and long-term complications. Diagnosis is based on ultrasound examination and treated with hysteroscopy. This study evaluated the size of RPOC that can be related to a positive pathology result for residua. Materials and methods This retrospective cohort study included women who underwent hysteroscopy for postpartum RPOC diagnosed by ultrasound, 4/2014-4/2022. Demographics, intrapartum, sonographic, intraoperative, and post-operative data were retrieved. We generated a ROC curve and found 7 mm was the statistically sonographic value for positive pathology for RPOC. Data between women with sonographic RPOC ≤ 7 mm and > 7 mm were compared. Positive and negative predictive values were calculated for RPOC pathology proved which was measured by ultrasound. Results Among 212 patients who underwent hysteroscopy due to suspected RPOC on ultrasound, 20 (9.4%) women had residua ≤ 7 mm and 192 (90.6%) had residua > 7 mm. The most common complaint was vaginal bleeding in 128 cases (60.4%); more so in the residua > 7 mm group (62.5% vs. 40%, p = .05). Among women with residua ≤ 7 mm, the interval from delivery to hysteroscopy was longer (117.4 ± 74.7 days vs. 78.8 ± 68.8 days, respectively; p = .02). Positive pathology was more frequent when residua was > 7 mm. PPV for diagnosis of 7 mm RPOC during pathology examination was 75.3% and NPV 50%. Conclusions Sonographic evaluation after RPOC showed that residua > 7 mm was statistically correlated with positive RPOC in pathology and PPV of 75% and NPV of 50%. Due to the high NPV and low complication rate of office hysteroscopy, clinicians should consider intervention when any RPOC are measured during sonographic examination to reduce known long-term complications.